Impact of visceral adiposity index on cognitive impairment and cognitive trajectories in Chinese middle-aged and older adults - Chen, Siran; Zhou, Mengqi; Han, Lin; Ma, Rui; Jiang, Xiaoyue; Yang, Ziyi; Du, Yuling; Yang, Yanfang (Frontiers in Public Health, 2025)
IntroductionThe association between the visceral adiposity index (VAI) and cognitive function in middle-aged and older Chinese adults is not well understood. The “obesity paradox”—where obesity appears to be linked with better health outcomes—has also been observed. This study aims to clarify the association by using data from a nationally representative longitudinal survey.MethodsThis study analyzed five waves of data from the China Health and Retirement Longitudinal Study (CHARLS) from 2011 to 2020. The Cox proportional hazards regression model was used to assess the effect of VAI on the occurrence of cognitive impairment. Additionally, cognitive trajectories over the study period were identified using group-based trajectory modeling (GBTM), and the association between VAI and cognitive trajectories was further analyzed through multinomial logistic regression.ResultsA total of 5,637 participants aged ≥45 years were included, of whom 46.6% were women. The risk of cognitive impairment was lower in participants with higher VAI scores (Q3: HR = 0.79, 95% CI: 0.67–0.94; Q4: HR = 0.83, 95% CI: 0.70–0.98). Cognitive trajectories over the 9-year period were categorized into four groups based on cognitive Z-scores: “high and stable” (n = 621, 12.6%), “middle and stable” (n = 2,157, 36.7%), “low and stable” (n = 1,856, 32.8%), and “low and decline” (n = 1,003, 17.9%). After adjusting for demographic and health-related variables, participants in the highest VAI quartile (Q4) had a significantly lower likelihood of experiencing cognitive decline (adjusted OR = 0.67, 95% CI: 0.48–0.93).ConclusionGreater visceral adiposity was associated with a lower risk of developing cognitive impairment and a more favorable cognitive trajectory over time.